Optimasi Pertumbuhan Miselium Jamur Tiram (Pleurotus astreatus) dengan Penambahan Nutrisi Jerami Padi Terintegrasi dengan Model Inokulasi - Jumriani, Siti; Musdalipah; Wahyuni, Sri; Rahmadinah, Nurul Afifah; Dahliah; Manguntungi, Baso; Ariandi; Sari, Arlinda Puspita; Ramlah (Undiksha, 2023)
Pleurotos ostreatus cultivation is a business opportunity that has high economic value and has increased every year. This study aims to determine the best planting inoculation method and surface method for Pleurotos ostreatus cultivation, and determine the most effective concentration of sawdust and straw mixed media for the growth of Pleurotos ostreatus. This study used a completely randomized design (CRD) with 2 factorials, namely surface inoculation and planting. The results showed that the cultivation of Pleurotos ostreatus using straw waste media as a replacement medium based on inoculation planting systems and surfaces including the stages of sterilization of tools and materials, making media, inoculation, incubation obtained the best model results, namely planting inoculation. Results Addition of straw media as a replacement medium based on the inoculation of the planting system and surface. After observing, the results of the most effective concentration or treatment for the growth of Pleurotos ostreatus were in the J3 treatment using the inoculation method of planting at 20.10 cm.